Decoding Employee Disengagement: The 4P Model of People, Process, Purpose, and Power - Shinde, Shilpa (Revista Review Index Journal of Multidisciplinary, 2025)
Employee disengagement poses a significant challenge for organizations worldwide, adversely affecting productivity, innovation, morale, and retention. Existing models often fall short in capturing the complex, interconnected causes of disengagement. This article introduces the 4P Model—People, Process, Purpose, and Power—as a comprehensive framework to understand and address employee disengagement from psychological, behavioural, and organizational perspectives. The model emphasizes the dynamic interactions among its components, highlighting how deficiencies in one area can exacerbate issues in others, creating feedback loops that deepen disengagement. Through this integrative lens, the 4P Model serves as a diagnostic tool for HR managers and organizational leaders to identify early warning signs and design targeted re-engagement strategies. Practical interventions tailored to each dimension, combined with strong leadership and continuous feedback mechanisms, can effectively restore employee motivation and commitment. Additionally, the model’s adaptability to diverse industries and cultural contexts underscores its utility as a versatile framework for enhancing organizational resilience and workforce well-being. This research contributes a strategic approach to managing disengagement, fostering sustainable engagement, and improving overall organizational performance.